Integrasi agama dalam pembelajaran sains di Madrasah - Tahir, Muhmmad Tarmizi (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Abstract This study aims to analyze how the concepts and forms of implementation of religious integration in science learning (biology, mathematics, physics and chemistry subjects) at Madrasah Aliyah Mu'allimin Nahdlatul Wathan Pancor Kab. East Lombok, West Nusa Tenggara Province (NTB) -Indonesia. By using a descriptive-analytic qualitative research method, data was collected through document techniques, interviews, and observation to explore data about the integration and internalization of Islamic values, namely the values of monotheism, shari'ah, morals and the development of science into students which has implications on the behavior and spirit of the use of knowledge (axiology of science) of students. Science strengthens and supports beliefs about God as the creator of the universe, while religion strengthens and directs science to provide benefits and fulfill the needs of human life. With the apologetic integration model, namely the integration model based on the view that science is a product that is universal and value-free. Therefore it can be used and applied anywhere and in any environment. In terms of the integration of science and technology and imtak, it seeks to legitimize the results of modern science by finding appropriate verses of the Koran, associated with Islamic values with scientific theory and existing in religious teachings.